As close as sisters - Faulkner, Colleen (Kensington Books, 2014)
Diagnosed with terminal cancer, 42-year-old McKenzie Arnold, spending one last summer with her three best friends, realizes that with the love and support of Aurora, Janine and Lilly, she can face her death with courage, but nothing has prepared her for how the summer will end.